Peningkatan Angka Perceraian Di Indonesia: Faktor Penyebab Khulu’ dan Akibatnya - Muhammad Sholeh (Prodi Ahwal Syakhsiyah, Fakultas Syariah, Institut PTIQ Jakarta, 2021)
The high divorce rate and dominated by divorce (khulu') in Indonesia has attracted the attention of many people. This study aims to analyze the provisions for divorce according to Islam and the laws and regulations and the factors that cause divorce in the Lubuklinggau Religious Court from 2013-2015. Analysis of research data with a qualitative approach by describing it descriptively to obtain a clear picture of understanding. The results showed that the factors causing divorce in a period of three years (2013-2015) were no harmony 5419 (37.6%), economic factors 3721 (25.8%), no responsibility 3191 (22.1%), third party interference 1458 (10.1%), persecution 443 (3.0%), unhealthy polygamy 88 (0.6%), and jealousy factor 36 (0.25%). The most dominant factor causing divorce in the Lubuklinggau Religious Court is that there is no harmony in the household which occupies the highest number compared to other causal factors.